EFFICIENCY OF GROWTH AND NUTRIENT UPTAKE FROM WASTEWATER BY HETEROTROPHIC, AUTOTROPHIC, AND MIXOTROPHIC CULTIVATION OF CHLORELLA VULGARIS IMMOBILIZED WITH AZOSPIRILLUM BRASILENSE1 - Perez‐Garcia, Octavio; De‐Bashan, Luz E.; Hernandez, Juan‐Pablo; Bashan, Yoav (Journal of phycology, 2010)
Heterotrophic growth of microalgae presents significant economic advantages over the more common autotrophic cultivation. The efficiency of growth and nitrogen, phosphorus, and glucose uptake from synthetic wastewater was compared under heterotrophic, autotrophic, and mixotrophic regimes of Chlorella vulgaris Beij. immobilized in alginate beads, either alone or with the bacterium Azospirillum brasilense. Heterotrophic cultivation of C. vulgaris growing alone was superior to autotrophic cultivation. The added bacteria enhanced growth only under autotrophic and mixotrophic cultivations. Uptake of ammonium by the culture, yield of cells per ammonium unit, and total volumetric productivity of the culture were the highest under heterotrophic conditions when the microalga grew without the bacterium. Uptake of phosphate was higher under autotrophic conditions and similar under the other two regimes. Positive influence of the addition of A. brasilense was found only when light was supplied (autotrophic and mixotrophic), where affinity to phosphate and yield per phosphate unit were the highest under heterotrophic conditions. The pH of the culture was significantly reduced in all regimes where glucose was consumed, similarly in heterotrophic and mixotrophic cultures. It was concluded that the heterotrophic regime, using glucose, is superior to autotrophic and mixotrophic regimes for the uptake of ammonium and phosphate. Addition of A. brasilense positively affects the nutrient uptake only in the two regimes supplied with light.